2012
DOI: 10.17763/haer.82.4.4u5v1n8q67332v03
|View full text |Cite
|
Sign up to set email alerts
|

Rules of the Culture and Personal Needs: Witnesses' Decision-Making Processes to Deal with Situations of Bullying in Middle School

Abstract: This article explores the decision-making processes by which early adolescents choose a strategy to upstand, bystand, or join the perpetrators when they witness situations of physical and relational bullying in their schools. Authors Silvia Diazgranados Ferráns, Robert L. Selman, and Luba Falk Feigenberg analyze data from twenty-three interviews conducted with eighth graders in four middle schools using a grounded theory approach and propose an emerging theoretical framework to guide future research on bullyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Interestingly, many of the barriers and facilitators of bystander action in situations of dating and sexual aggression we documented are similar to barriers and facilitators of bystander action documented in the bullying literature (Ferrans et al 2012;Pozzoli and Gini 2010a, b;Pozzoli et al 2012). Girls were more likely than boys to intervene in situations of dating and sexual aggression, which is consistent with previous research (Jaffe et al 1992;Van Camp et al 2014).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, many of the barriers and facilitators of bystander action in situations of dating and sexual aggression we documented are similar to barriers and facilitators of bystander action documented in the bullying literature (Ferrans et al 2012;Pozzoli and Gini 2010a, b;Pozzoli et al 2012). Girls were more likely than boys to intervene in situations of dating and sexual aggression, which is consistent with previous research (Jaffe et al 1992;Van Camp et al 2014).…”
Section: Discussionsupporting
confidence: 76%
“…Reasons for non-action were primarily because youth believed it was not their business or concerns they would get hurt or in trouble. Although specific to bullying, Ferrans et al (2012) conducted in-depth interviews with 8th graders and found that bystander action was impacted by youth's interpretation of the underlying nature of the situations (e.g., joke vs. gone too far), relationship with the victim and perpetrator, feelings of moral responsibility, and power status in the relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from this study also suggest that more research is needed to better understand the complexities of bystander behaviors. As has been found in previous research, our study finds that bystander behavior is clearly affected by social relationships and the context of the harassment and bullying (Ferráns et al 2012). It is likely that victims' interpretation of bystander behavior and its impact on them will similarly be influenced by context.…”
Section: Implications For Prevention and Researchsupporting
confidence: 85%
“…Emerging research shows that the nature of the aggression and the relationship between the victim, perpetrator and bystander are important influences on how a bystander responds (Nishina and Bellmore 2010). One study found that bystander strategies for a victimization event are influenced by a combination of person-level variables, and cultural rules and influences at the friendship level, the peer group level, and the institutional level (e.g., school) (Ferráns et al 2012). Narrowing bystander behavior to a few possible roles when directly witnessing a bullying or harassment incident in person may miss much of the social dynamics that typify the complexity of many youth harassment and bullying experiences.…”
Section: The Complexity Of Bystander Behaviormentioning
confidence: 99%
“…Although appearing as logical and rational methods for children to employ, these strategies occasionally backfire for victims. From children's perspectives, reporting the incident to a trusted school adult is an unfavourable tactic for a variety of reasons (Berger, 2007;Ferráns et al, 2012): (a) adults may mismanage the situation, (b) adults make no difference to the situation, (c) adults do not understand the child's perspectives and feelings, (d) children fear causing trouble for others, and (e) adults sometimes exacerbate the situation. When experiencing bullying, children much prefer seeking support from a friend, rather than school authority.…”
Section: Strategies To Manage Bullying Encountersmentioning
confidence: 99%